1997
DOI: 10.1155/mbd.1997.267
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biological Behaviour of Co(II), Cu(II) and Ni(II) Metal Complexes of Some Amino Acid Derived Schiff‐Bases

Abstract: Biologically active tridentate amino acid (Alanine, Glycine & Tyrosine) derived Schiff-bases and their Co(II), Cu(II) & Ni(II) complexes have been synthesised and characterised on the basis of their conductance and magnetic measurements, elemental analysis and 13C-NMR, 1H-NMR, IR and electronic spectral data. These Schiff-bases and their complexes have been evaluated for their antibacterial activity against bacterial species such as Staphylococcus aureus, Escherichia coli, Klebsiella pneumonae, Proteus vulgaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 1 publication
1
31
0
Order By: Relevance
“…[2][3][4]. And also, their metal complexes often exhibit antibacterial, antiviral, fungicidal or antitubarculoral activity [5,6]. In the title compound, C17H 12 N 2 O 3 , the naphthalen and phenyl ring groups are planar with an r.m.s.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]. And also, their metal complexes often exhibit antibacterial, antiviral, fungicidal or antitubarculoral activity [5,6]. In the title compound, C17H 12 N 2 O 3 , the naphthalen and phenyl ring groups are planar with an r.m.s.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from biological activities, Schiff bases are also used as catalysts, intermediates in organic synthesis, dyes, pigments, polymer stabilizers [3], and corrosion inhibitors [19]. Studies enlightened that metal complexes show greater biological activity than free organic compounds [20]. Augmentation of biological activity was reported by implementation of transition metals into Schiff bases [21].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids and their compounds with different metal ions play an important role in biology, pharmacy, and industry [7][8][9][10][11][12]. It has been reported that metal complexes of amino acid Schiff bases with transition metals possess anticarcinogenic [13], antimicrobial [14], and antitumor [15] activity.…”
Section: Introductionmentioning
confidence: 99%